Prevalence and correlates of underweight and overweight/obesity among women in India: results from the National Family Health Survey 2015–2016 - Pengpid S (Dove Medical Press, 2019)
Supa Pengpid,1,2 Karl Peltzer21ASEAN Institute for Health Development, Mahidol University, Salaya, Nakhonpathom, Thailand; 2Deputy Vice Chancellor Research and Innovation Office, North West University, Potchefstroom, South AfricaObjective: The study aimed to assess the prevalence and correlates of underweight and overweight or obesity among women in India.Subjects and methods: In a population-based cross-sectional 2015–2016 National Family Health Survey, ever married non-pregnant women (18–49 years) were interviewed and assessed with anthropometric, blood pressure and biochemical measures.Results: The total sample included 5,82,320 non-pregnant women 18–49 years, median age 31 years, interquartile range =16 years, from India. Overall, 20.1% of the women were underweight [body mass index (BMI) m2,] and 36.3% were overweight, or had class I or class II obesity (BMI ≥23.0 kg/m2,). In adjusted multinomial logistic regression, younger age, lower education, lower wealth status, not eating daily fruits, vegetables, fried food, belonging to the scheduled tribe and tobacco use were associated with underweight, while older age, higher education, higher wealth, belonging to other backward class or other, urban residence, daily fruit consumption, daily fried food consumption, having hypertension, heart disease and high or very high blood glucose levels were associated with overweight or obesity. Belonging to the scheduled caste and tobacco use were negatively associated with overweight or obesity.Conclusions: A high dual burden of both underweight and overweight or obesity was observed among women in India. Sociodemographic and health variables were identified as risk factors for both underweight and overweight or obesity, which can be utilized in informing intervention strategies.Keywords: women, underweight, overweight, obesity, health variables, India